Bone diagenesis at the Florisbad spring site, Free State Province (South Africa): Implications for the taphonomy of the Middle and Late Pleistocene faunal assemblages. (December 2015) - Toffolo, Michael B.; Brink, James S.; Berna, Francesco
Abstract: The Middle to Late Pleistocene spring site of Florisbad, South Africa, is the name site of the Florisian Land Mammal Age (LMA), and it has produced a large collection of fossil bones from different sedimentary contexts. The largest of these faunal assemblages derives from vertically intrusive dormant spring vents and is taphonomically distinct from specimens associated with a Middle Stone Age occupational horizon. The Florisbad faunal assemblages include several extinct and extant animal species, mainly grazing ungulates that represent a highly productive open grassland environment. The Florisian LMA was characterized by substantially wetter conditions compared to the Holocene. Geological evidence at Florisbad and the characteristic occurrence of water-dependent species, such as lechwe, waterbuck, hippopotamus and a variety of water birds, reflect the presence of a vast intermittent paleolake forming during the wet phases of the Middle and Late Pleistocene. During dry phases, the area of spring activity was not inundated and provided a suitable habitat for both humans and animals. Bones collected from different sedimentary contexts exhibit a number of post-depositional alterations that reflect specific diagenetic processes, which led to fossilization. Two contrasting hypotheses regarding these processes, based on morphological studies of bones and groundwater chemistry, were proposed in the past. The first identified spring water as a major fossilization agent, whereas the second saw it as a medium conducive to bone dissolution. Using Fourier Transform infrared spectrometry (FTIR) and micro-spectrometry (μFTIR), we determined the mineralogical composition of these bones. We show here that specimens from inactive paleo-spring vents are characterized by the formation of carbonate fluorapatite on the outer surface of cortical bone, and locally exhibit authigenic calcite crystals, as opposed to bones collected from non-spring contexts at the site. The nucleation of carbonate fluorapatite is linked to the high fluoride content of the alkaline spring water, thus confirming its key role in the fossilization process of bones recovered from paleo-spring vents. Therefore, our results support the first of the two hypotheses advanced in the past. Highlights: Fossil bones were recovered from different MSA sedimentary contexts at Florisbad. Two contrasting hypotheses about the fossilization processes of bones were proposed. We analyzed bone samples using FTIR spectrometry to reconstruct diagenetic paths. Bones collected from extinct spring vents were mineralized by local spring water. We determined the diagenetic processes and confirmed one of the two hypotheses.